IP over optical cross-connect architectures. - Guangzhi Li.
IP over optical network architectures have been extensively discussed within the research literature over the past few years. However, although signaling protocols between IP routers and optical cross-connect networks have been standardized, large IP backbones are not typically deployed over optical cross-connect networks with automatic reconfigurability features, such as automatic restoration or dynamic establishment of new IP links. One of the most important criteria in determining whether an IP backbone should be carried over such an optical cross-connect network is economic viability. In this article we analyze and explore four architectures for a typical large ISP backbone. In contrast with some other published claims, our results suggest it is more economically attractive to bypass an intermediate cross-connect network, given current equipment and IP backbone network design requirements. However, for ISPs who also provide a large volume of private line services, we propose an integrated architecture for IP over optical cross-connect networks that may provide an attractive alternative for providing rapid and cost-effective restoration from network failures.
Keywords: IP over optical cross-connect network architectures; IP routers; ISP backbone; Automatic IP link restoration; Automatic recofigurability features; Dynamic IP link establishment; Network failures; Private line services; Signaling protocols